Human brown fat, adiposity, and cardiometabolic health: New pieces to the puzzle - Chondronikola, Maria (Cell Rep Med, 2021)
Brown adipose tissue (BAT) is an emerging target against obesity and its related metabolic diseases. Wibmer et al.(1) recently reported that human BAT is associated with a healthier fat distribution and improved cardiometabolic health independent of adiposity and fat distribution.